HUBUNGAN MOTIVASI KERJA INSTRINSIK PEGAWAI DAN MOTIVASI KERJA EKSTRINSIK DENGAN PRODUKTIVITAS KERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN TABANAN - Sutama, I Wayan (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Research on the productivity of employees working in the Department of Populationand Civil Registration of Tabanan Regency is based on the promise that publicorganizations today must run a really professional job functions as well as increasedefforts to public service more accountable and transparent. The most fundamentalissue related to human resources in the public sector is the low level of employees’productivity so there is an impression that the public sector is currently seem morelikely to be served rather than serving. This study uses a quantitative approach totest the relationship between the variables studied, where the specifics of this studyexamined the relationship of intrinsic and extrinsic work motivation with theproductivity of employees working in the Department of Population and CivilRegistration of Tabanan Regency. Number of employees used as sample in this studywas 50 employees, who all served in the Department of Population and CivilRegistration of Tabanan Regency. The sampling technique is done by using arandom sampling technique. The results showed that the productivity of employeesin the Department of Population and Civil strongly related to intrinsic job motivationand extrinsic work motivation. To improve the level of employee discipline, effortsto increase employee motivation and productivity seems very important to do.Judging from the increase in work motivation aimed at productivity levels ofemployees in achieving organizational performance. In terms of motivation, theawards system for employee’s job performance is also very important to note. Theseefforts need to be done as soon as possible so that the productivity of employeesworking in the Department of Population and Civil Registration of Tabanan Regencycan be improved, which is of course in the end it will be able to give a positiveimpact in terms of improving organizational performance.